1974
DOI: 10.1099/00221287-85-1-37
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Aromatic Metabolism in the Fungi: Metabolic Control of the 3-Oxoadipate Pathway in the Yeast Rhodotorula mucilaginosa

Abstract: SUMMARYThe metabolic control of the protocatechuate branch of the 3-oxoadipate pathway in Rhodotorula mucilaginosa was examined and the specific inducers identified using appropriately blocked mutants. Three successive inductive events permitted the synthesis of the five enzymes converting p-hydroxybenzoate to 3-oxoadipyl-CoA: the independent induction of 4-hydroxybenzoate 3-monooxygenase by its own specific substrate, the independent induction of protocatechuate 3,4-dioxygenase by either protocatechuate or p-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…52 This organism appears to express proteins belonging to the protocatechuate branch of the β-ketoadipate degradation pathway but lacks enzymes of the catechol branch, and it is therefore unable to metabolize catechol. 53 One drawback for this organism is that there are few genetic tools currently available for red yeasts compared to P. putida and C. glutamicum, and therefore a more extensive effort is required to pursue genetic engineering strategies in this organism.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…52 This organism appears to express proteins belonging to the protocatechuate branch of the β-ketoadipate degradation pathway but lacks enzymes of the catechol branch, and it is therefore unable to metabolize catechol. 53 One drawback for this organism is that there are few genetic tools currently available for red yeasts compared to P. putida and C. glutamicum, and therefore a more extensive effort is required to pursue genetic engineering strategies in this organism.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Preparation of cell-free extracts and measurement of the relevant enzymes are described in detail in the following paper (Cook & Cain, 1974 Preparation of nystatin. Nystatin (Nystan, E. R. Squibb & Sons, Liverpool) was prepared as a suspension in water at 2 mg/ml and the pH adjusted to 8-5 with 5 M-NaOH.…”
Section: Mutagenesismentioning
confidence: 99%
“…Some filamentous fungi (Jones et al, 1995), algae (Semple and Cain, 1996), and higher plants (Prasad and Ellis, 1978) have been reported to be able to degrade phenol. Reports on the decomposition of phenolic compounds by yeasts are scanty when compared to those on bacteria (Anderson and Dagley, 1980;Cook and Cain, 1974;Gaal and Neujahr, 1981;Hirayama et al, 1994;Hofmann and Vogt, 1987) and in all of the cases reported, the utilization of phenols was limited and slow. Middelhoven (1993) has made an extensive study on the metabolism of aromatic compounds by ascomycetous and basidiomycetous yeasts and yeastlike fungi, and demonstrated that the catechol branch of the 3-oxoadipate pathway and its hydroxyhydroquinone variant were involved in phenol and resorcinol catabolism of ascomycetes as well as of basidiomycetes.…”
Section: Introductionmentioning
confidence: 99%